1988
DOI: 10.2165/00003088-198814010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Clinical Use of Flumazenil (Ro 15-1788)

Abstract: Flumazenil (Ro 15-1788) is a specific benzodiazepine antagonist which can prevent or abolish selectively at the receptor level all centrally mediated effects of benzodiazepines. Following oral administration flumazenil is rapidly absorbed (peak concentrations are achieved after 20 to 90 minutes), but bioavailability is low (16%) due to significant presystemic elimination. As less than 0.2% of an intravenous dose was recovered as unchanged drug in the urine, extensive metabolism must occur and so far 3 metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 53 publications
1
54
1
Order By: Relevance
“…We therefore further investigated the interaction of ciprofloxacin, norfloxacin and ofloxacin with the benzodiazepine (BZD)-GABAAreceptor complex in a radio-receptor assay (RRA) either the short-acting BZD-agonist midazolam (Allonen et al, 1981) or the specific BZDantagonist flumazenil (Klotz & Kanto, 1988 Subjects/Study design After obtaining written informed consent, 12 drug-free healthy volunteers (three females, nine males) between 23 and 47 years old participated in the study, which was approved by the Ethics committee of our hospital. Inclusion criteria were normal values in the haematological, physical and clinical safety checkups and a stable alpha-rhythm with an alpha proportion > 40%, evaluated in an EEG pre-screening.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore further investigated the interaction of ciprofloxacin, norfloxacin and ofloxacin with the benzodiazepine (BZD)-GABAAreceptor complex in a radio-receptor assay (RRA) either the short-acting BZD-agonist midazolam (Allonen et al, 1981) or the specific BZDantagonist flumazenil (Klotz & Kanto, 1988 Subjects/Study design After obtaining written informed consent, 12 drug-free healthy volunteers (three females, nine males) between 23 and 47 years old participated in the study, which was approved by the Ethics committee of our hospital. Inclusion criteria were normal values in the haematological, physical and clinical safety checkups and a stable alpha-rhythm with an alpha proportion > 40%, evaluated in an EEG pre-screening.…”
Section: Introductionmentioning
confidence: 99%
“…The first four patients received the entire dose of flumazenil in one nostril and, given the large volumes, it is conceivable that some, if not most, of the flumazenil was absorbed via the gastrointestinal tract. This would result in first pass hepatic metabolism with reduced bioavailability, as reported by Klotz et al .,4 where oral flumazenil has a bioavail -ability of only 16%. Indeed, the pharmacokinetic analysis of the final six patients yielded a peak plasma concentration that was 50% greater than that of the whole study group.…”
Section: Discussionmentioning
confidence: 91%
“…Klotz et al . 4 concluded that plasma concentrations of 10 to 20 ng·mL -1 may effectively reverse BZD induced CNS depression. In another study, the mean plasma concentration of flumazenil required to reverse midazolam, as measured by the ability of the patient to identify him-or herself verbally after midazolam anesthesia, was 29.9 ng·mL -1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations